Community service order as alternative punishment in Syariah court: an analysis - Abas, Afridah; Hussin, Nasimah (Universiti Putra Malaysia Press, 2017)
Syariah courts in Malaysia have the jurisdiction to impose punishments up to 3 years imprisonment, 6 strokes and RM5000 fi ne or combination of any two or three of the punishments (Criminal Jurisdictions) Act (Amendment 1984). Referring to Syariah Criminal Offences Act, Syariah Court Judge has the discretion to impose punishment for fi rst offender, youthful offender, woman offender and those who has previous conviction. The judge can consider light punishments as an alternative to the punishment provided for that particular offence. Hence, a judge can use his discretion to order for good behaviour or send the offender to rehabilitation centre/approved home. This paper seeks to examine the possibility of the Syariah Court to give an order of community service as an alternative punishment. This research is basically qualitative and analysis based on the discussions of the implementation of a community service order as practised by civil courts.